1994
DOI: 10.1016/0735-1097(94)90419-7
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular ultrasound detection of atherosclerosis at the site of focal vasospasm in angiographically normal or minimally narrowed coronary segments

Abstract: These results indicate that atherosclerosis is present at the site of focal vasospasm, even in the absence of angiographically significant coronary disease. We suggest that the existence of such atherosclerotic lesions is related to the occurrence of focal vasospasm in the clinical settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
84
1
3

Year Published

1994
1994
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(97 citation statements)
references
References 19 publications
9
84
1
3
Order By: Relevance
“…The characteristics of the lesion that is the culprit of coronary spasm are the existence of minimal atherosclerosis, with relatively low-echo intensity, less calcification, and negative remodeling on IVUS images. [6][7][8][9][10] In our case, the IVUS image at the occlusion site shared some of the above previously reported IVUS characteristics of a spasm-induced vessel site: minimal atherosclerosis and less calcification.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The characteristics of the lesion that is the culprit of coronary spasm are the existence of minimal atherosclerosis, with relatively low-echo intensity, less calcification, and negative remodeling on IVUS images. [6][7][8][9][10] In our case, the IVUS image at the occlusion site shared some of the above previously reported IVUS characteristics of a spasm-induced vessel site: minimal atherosclerosis and less calcification.…”
Section: Discussionsupporting
confidence: 61%
“…4,5) Previous intravascular ultrasound (IVUS) and optical coherence tomography (OCT) studies have reported the morphological features of vasospastic lesions. [6][7][8][9][10][11] However, most of the data were obtained in a spastic lesion that was artificially induced by the administration of a vasoconstrictor (acetylcholine or ergonivine). In the present report, we report IVUS images from a patient with ST elevation type acute myocardial infarction (STEMI) due to vasospasm.…”
mentioning
confidence: 99%
“…Nissen reported on intravascular US of the coronary arteries, which was found to be a promising technique without significant risk (15). In a study of angiographically normal sites in coronary artery disease patients, Yamagishi et al found that more than 75% had atherosclerotic abnormalities at US, emphasizing that coronary disease is often more diffuse than indicated by angiography (16). In a recent randomized trial comparing intensive and moderate lipid-lowering therapy on the progression of coronary atherosclerosis, IVUS successfully identified significant changes in the artery wall (17).…”
Section: Introductionmentioning
confidence: 99%
“…Spasm may also occur in proximity to atherosclerotic lesions including small lesions (2). Patients are often heavy cigarette smokers (3).…”
Section: Figure 1) a Electrocardiogram (Ecg) On Arrival (Precordial Lmentioning
confidence: 99%